In vitro establishment and multiplication of mountain papayas: Vasconcellea chachapoyensis and Vasconcellea x heilbornii (Bioagro, 2021)
The application of tissue culture techniques in Vasconcellea species is a viable alternative for the propagation of these species. However, the efficiency of these tools is conditioned by factors such as contamination of explants, the effect of growth regulators and the species to be propagated. The present study aimed to evaluate sterilization protocols with different concentrations of NaClO and Ca(ClO)2 as well as different immersion times for the aseptic establishment of explants. Likewise, it was evaluated the action of the phytohormones BAP, ANA and AG3 in different concentrations in the in vitro multiplication of nodal segments of Vasconcellea chachapoyensis and Vasconcellea x heilbornii. The experiments were conducted under a completely randomized design with factorial arrangement, and the data were analyzed with the Kruskal Wallis test. The results showed that when using 1.5 % NaClO for 10 min, only 10 % contamination occurred, with V. chachapoyensis being the species that achieves the highest viability of explants in the establishment stage. On the other hand, the medium supplemented with BAP generated a greater number of shoots and leaves, while AG3 induced greater shoot elongation. In addition, it is worth mentioning that the species influenced multiplication, with V. x heilbornii being the species with the best morphological development. These results indicate the efficacy and importance of disinfectants and growth regulators during tissue culture, being a favorable alternative for the micropropagation of species of the genus Vasconcellea.
Keywords: Tissue culture; explant disinfection; plant growth regulators; nodal segments; Vasconcellea